A Comparison between Human Translation and Machine Translation in Fitness 24/7: (Perbandingan Terjemahan Manusia dan Terjemahan Mesin dalam Buku Fitness 24/7) (Jurnal Bahasa, 2015)
This research intended to study the similarities between human translation and machine translation in translating technical texts. The functional approach of Christian Nord (1997) was applied in this study. For human translation, the text analysis method was used on the chosen book, Fitness 24/7 (2008), which was translated into Malay by Kevin Zahri as Cergas 24/7 (2008), while Google Translate was selected for the machine translation. Several similarities, such as word choice, sentence structure and overall meaning of sentences were singled out by the researcher for this study. The results obtained from this research show that the similarities between human and machine translation in translating technical texts are minimal, at only 36.1 percent. This proves that machine translation generates a different text translation when compared to human translation. Hence, human expertise is still required to produce a superior translated text.Keywords: aspects of similarity, human translation, machine translation, technical text